Universal Islamic Education in the Regulation of Da’wah Orientation of Majelis Taklim in Indonesia - Widoyo, Agus Fatuh; Islamy, Athoillah; Zulihi, Zulihi; Susilo, Adib (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The presence of the Minister of Religious Affairs Regulation in regulating the da’wah activities of the Majelis Taklim in Indonesia has reaped resistance. There are some negative opinions by Muslims who consider the Minister of Religious Affairs Regulation contains intervention, discrimination, and even bad stigma against the da’wah activities of the Majelis Taklim in the community. This qualitative study with a normative-philosophical approach aims to identify the content of universal Islamic Education values in the da’wah orientation of the Taklim Council in Indonesia in the Regulation of the Minister of Religious Affairs no. 29 of 2019 concerning the Majelis Taklim. Study data were collected through documentation techniques. Meanwhile, data analysis through reduction, presentation, and verification.This study concludes that there is a content of universal Islamic education values in regulations on the orientation of the Majelis Taklim in Indonesia, including the value of tafahum on the development of personality characters that respect human values, and religion. Furthermore, the value of tasamuh in the development of personality characters that respect social pluralism. Next, takaful value in the development of personality characters that maintain the integration of state life. This study affirm that the values of universal Islamic education can be disseminated in the Indonesian government's policy regarding the orientation of educational institutions and Islamic da’wah in a plural social life.